Building Leadership in Project and Network Management A Facilitator's Toolset - Franz, Hans-Werner (Management for Professionals,, 2018)
This book introduces readers to essential facilitation techniques for leadership in the contexts of project and network management. It provides method-based messages, a facilitator curriculum, and a veritable arsenal of 50 carefully selected and 'reality-tested' tools for facilitation in non-hierarchical contexts. As such, readers will benefit just as much from learning by doing as from doing by learning. This book is also intended for all managers who are responsible for successful communication and co-operation in projects in and across organisations or networks of organisations, and who want to know how to share their plans effectively and improve collaboration. Though the book employs scientific principles, it is chiefly a practical guide, and draws on the authors' extensive experience in consultancy and management.